(untitled) (Conference on English Language Teaching, 2025)
This study explores the effectiveness of Mobile-Assisted Language Learning (MALL) in improving students’ English language skills in EFL (English as a Foreign Language) classrooms. Using a quantitative approach, data were collected through questionnaires involving 20 students and analyzed using statistical tests, including one-sample t-tests, Pearson correlations, and multiple linear regression. The results show that mobile applications significantly impact students’ English language skills (r = 0.770, p < 0.01) and serve as a primary predictor of learning motivation (β = 0.744, p < 0.01). However, the average English language proficiency (mean = 29.8) and learning motivation through mobile applications (mean = 23.3) remain below the reference value (40).Interestingly, the impact of socioeconomic status on English proficiency and students’ motivation was found to be insignificant (p > 0.05), indicating that equal access to technology can reduce social disparities in technology-based learning. This study underscores the significant potential of MALL in enhancing English skills, emphasizing the need for optimizing applications with interactive features and personalization. Recommendations include increasing the intensity of application use, training teachers in technology integration, and implementing inclusive policies to support students from diverse socioeconomic background.